Database development for water quality index using geographical information system - Nadia Natasha Salim,; Mustaffa Anjang Ahmad,; Nasradeen A Khalifa,; Adel Al-Gheethi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study aimed to identify drainage pollution at Parit Raja, Johor in accordance to the Water Quality Index (WQI) and based on Geographic Information System (GIS) data analysis. A total of 18 sampling stations at six drainage ditches were selected to be sampling points. The parameters investigated included Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Suspended Solid (SS), Ammonia Nitrogen (AN) and pH. ArcGIS software was selected and the water quality data were gathered and digitized in the GIS as data storage system in order to develop database. The results revealed that 13 stations were categorized as polluted, 5 stations classified as slightly polluted. These findings indicated that GIS have an ability to provide interactive visual and attribute information effectively in order to improve water quality management system. Therefore, GIS can be applied on a big study area and this is useful for wastewater management by authorities.